Development of a cold atmospheric pressure plasma jet for surface treatment applications - De Leon, Mark Jeffry D.; Vasquez, Magdaleno R. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Cold atmospheric pressure plasma is a low temperature, non-vacuum plasma. Due to the absence of a vacuum system, treatment using atmospheric plasma is quicker and cheaper than low-pressure plasmas and it is capable of treating a wider array of surfaces. In this study, a cold atmospheric pressure plasma jet (CAPPJ) using a neon transformer as its power source was developed and its electrical, thermal, and optical properties were investigated. After testing several CAPPJ configurations, a chosen configuration was used to treat different representative surfaces. These substrates are polyvinyl chloride (PVC), paper, polyethylene naphthalate (PEN), aluminum, and bamboo. The surfaces were evaluated for the change in surface free energy and surface chemistry in order to assess the effectivity of the CAPPJ for surface treatment. The final device developed was a bare electrode arc discharge-based system powered by a 15 KV, 30 mA, 60 Hz neon transformer. This was then connected to a variable autotransformer to control the power delivered unto the plasma. The nozzle of the device was made out of polytetrafluoroethylene and the electrodes were made of stainless steel bolts. The process gases used were nitrogen and air. The flow of the gas was controlled by a flow meter and was fed through the nozzle, passing through a 1 mm gap between the electrodes and out of a 1 mm diameter hole where the plasma jet is ejected. The developed device was able to produce a 7 mm long air plasma plume and 24 mm long nitrogen plume that had a temperature of less than 60°C 5 mm from the nozzle. The discharge voltage for the plasma jet was found to be around 1.5 KV RMS and the waveform changed from sinusoidal to a square waveform with lower amplitude when the discharge was produced. The optical emission spectra show that the air plasma was composed of nitrogen and oxygen excited species while the nitrogen plasma showed mostly nitrogen species. The device was successfully used to treat the surfaces of the different materials. It was found that air and nitrogen plasma treatment increased both the hydrophilicity and the free energy of the surfaces. Plasma treatment was also able to induce changes in the chemistry of the surface as was seen in the evolution of new functional groups. In addition, adhesion was improved using plasma treatment, as evidenced by improved wetting and adhesion of water-based paint on plasma-treated PVC. Lastly, an improvement in adhesion strength using polyvinyl acetate glue on plasma-treated bamboo was realized from the single lap joint adhesive shear strength test. This work was able to demonstrate the development of a CAPPJ system using a low-frequency power source that can be used to treat different surfaces that may find practical industrial applications.
Thesis (Master of Science in Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Plasma jets; Atmospheric pressure; Surfaces (Technology).